The Potential of Utilizing the Arbuscular Mycorrhiza (AM) in the Rehabilitation of Sandy Tailings With Acacia Mangium Willd - Md. Jais, Hasnah (1997)
This study examined the potential of utilising the AM fungi and an organic fertiliser in improving the plant growth and soil fertility status of sandy tailings. The AM fungal spore and Most Probable Number (MPN) count and root infection ratings were determined in barren sandy tailings and sandy tailings under a five and seven year old A. mangium stands. The results indicate very slow build up of the AM propagules over a seven year period of rehabilitation. Glomus spp. was more widely distributed as compared to Gigaspora spp. Under the propagation trials, the pot culture method using Setaria spp. as the host was found to be most suitable for production of large scale inoculum. S. calospora, an introduced species was found to be the most effective with maximum 55% infection in the A. mangium roots.